If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 29 + -9x = 10x Solving 29 + -9x = 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 29 + -9x + -10x = 10x + -10x Combine like terms: -9x + -10x = -19x 29 + -19x = 10x + -10x Combine like terms: 10x + -10x = 0 29 + -19x = 0 Add '-29' to each side of the equation. 29 + -29 + -19x = 0 + -29 Combine like terms: 29 + -29 = 0 0 + -19x = 0 + -29 -19x = 0 + -29 Combine like terms: 0 + -29 = -29 -19x = -29 Divide each side by '-19'. x = 1.526315789 Simplifying x = 1.526315789
| +2x+2x=+5-3 | | 1500t+8=20t | | 3(2x-2)+3=3(2x+4) | | 10(8+2x)-5(1+5x)= | | 226=2(9+13n) | | x+2x-3=2 | | .5(4x+10)=6 | | 33r^2+10r-7=0 | | 4x^2-28x+24=0 | | -25-7f=8(2f+4) | | 3x+7=14+3x+2x | | 2x+5-4=3 | | -5(2x+1)=9 | | 2-(3x+5)=18-7x | | 3n+6=-24 | | 20x^2=-12x | | 324=-12(-6+3x) | | 3(13-6)=4(2-0.5b) | | 56+12m=60+8m | | 41/5=15-(2x+3) | | 3(4x+7)=14 | | 30-7x=10x-4 | | 6x+5=81 | | 2y-17=x | | -11(9+10a)=-1639 | | 2x-3+1=17 | | 0=x^2+13x-510 | | a^2-5a+ab-5b= | | 6x^2+8x-12=2x^2-3x+6 | | 6-a+b=4 | | 9y^2-17y+8=0 | | 16+5x=51 |